Desarrollo de una estrategia pedagógica para la enseñanza de arquitecturas micro-procesadas con base al núcleo RISC-V core101 (2020)
In this document is detailed the process followed to develop a new learning strategy for its use in the subject ?Architecture and design of digital systems? of the electronic engineering program. This strategy will allow to implement the original topics of the subject using the RISC-V ISA. The strategy?s objective was implemented on the virtual education environment caused by the COVID-19 pandemic and other methodologies of education that will be used in the future. The strategy includes the design of a module for the actual subject along with its own schedule and evaluation system, that will replace the education approaches used in the past. To achieve this goal, new class material was developed for improving the learning process of the students in the virtual environment.